Association of abortion history with the presence of anti-Neospora caninum antibodies in dairy cows - Tiago Andre Frigotto (Semina: Ciências Agrárias, 2018)
Neospora caninum is an important cause of abortions in dairy cattle, leading to severe economic losses. The objective of this study was to determine the association of serum antibodies against N. caninum with a history of abortion in dairy cows. A total of 46 dairy cows from nine dairy farms were evaluated; 28 with a history of one or more abortions and 18 without a history of abortions. Antibodies against N. caninum were detected by indirect immunofluorescence, and the reaction was considered positive when the titer was ≥1:50. Serum antibodies against N. caninum were detected in 39.1% (18/46) of all cows, 57.1% (16/28) of cows with a history of abortion, and 11.1% (2/18) of cows without a history of abortion. Among the seropositive cows, 88.9% had a history of abortion. All farms showed at least one animal positive for N. caninum. These results indicate an association between seropositivity for N. caninum and a history of abortion in cows. Cows with a history of abortion were 10.6 times more likely to be seropositive for N. caninum than cows without a history of abortion. Therefore, we concluded that there is an association between a history of abortion and the presence of antibodies against N. caninum in dairy cows.